Solution of a Scalar Two-Dimensional Nonlinear Diffraction Problem for Objects of Arbitrary Shape - A. O. Lapich; M. Y. Medvedik (Учёные записки Казанского университета: Серия Физико-математические науки)
In this study, the development, design, and software implementation of the methods for solving the nonlinear diffraction problem were performed. The influence of nonlinear medium defined by the Kerr law on the propagation of a wave passing through an object was examined. The differential and integral formulations of the problem and the nonlinear integral equation were considered. The problem was solved for different bodies with the use of various computational grids. Convergence graphs of the iterative processes were generated. The obtained graphical results were presented. The explicit and implicit methods for solving the integral equation were compared.